Comparison of Antioxidant Phenolics of Ethanolic Extracts and Aqueous Infusions from Sideritis Species - ozkan, Gulcan (Asian Journal of Chemistry, 2010)
Water and ethanol as solvents for the manufacture of foodstuffs or food ingredients is permissible and it could be extraction flavourings from natural flavouring materials safely. In this study, comparison of phenolic composition of ethanolic extracts and aqueous infusions from Sideritis caesarea Duman, Aytaç et Baser, Sideritis condensata Boiss. & Heldr., Sideritis ozturkii Aytac & Aksoy, Sideritis perfoliata Linnaeus and Sideritis pisidica Boiss. & Heldr. were investigated. The yields of water extracts (10.56-22.12 %) were higher than yields of ethanol extract (3.52-7.98 %). Eleven phenolic compounds in ethanolic extract and ten phenolic compounds in aqueous infusions were identified by HPLC. Naringin was the major compound for both extracts and higher in ethanol extracts (23.87-222.90 mg/100 g dried herb); while gallic acid, apigenin- 7-O-glucoside and eriodictiol were determined in only ethanol extracts, (+)-catechin and vitexin were in only water extracts. As a result, ethanol had higher performance for extracting phenolics but aqueous infusions more effective in extract yield.